Propuesta de actualización al plan de gestión integral de residuos sólidos, del municipio de Une - Cundinamarca (2021)
The municipality of Une - Cundinamarca, in compliance with Resolution 1045 of 2003 welcomed the Integrated Solid Waste Management System, through Municipal Decree No. 135 of 2015, provided by CORPORINOQUIA. To dispose of waste generated through the Doña Juana Landfill. However, to date some problems are visible, perhaps due to the lack of investment, socialization with the community, environmental awareness, Waste Management through the Public Services office starting with the generation, collection, transportation, storage, use and final disposal. Therefore, it is necessary to propose an update to the waste management plan to obtain a proposal for integrated waste management for the benefit of the environment, the economy and the community of the municipality. Through environmental education projects, awareness raising and activities that involve the participation of all the inhabitants. The work intends to be developed through qualitative methods related to the description of the baseline and diagnosis of the programs that are part of the provision of the sanitation service, quantitative methods such as statistical data on population projections, projections of solid waste generation and financial plan.